Multiscale metrologies for process optimization of carbon nanotube polymer composites. (November 2016) - Natarajan, Bharath; Orloff, Nathan D.; Ashkar, Rana; Doshi, Sagar; Twedt, Kevin; Krishnamurthy, Ajay; Davis, Chelsea; Forster, Aaron M.; Thostenson, Erik; Obrzut, Jan; Sharma, Renu; Liddle, J. Alexander
Abstract: Carbon nanotube (CNT) polymer nanocomposites are attractive multifunctional materials with a growing range of commercial applications. With the increasing demand for these materials, it is imperative to develop and validate methods for on-line quality control and process monitoring during production. In this work, a novel combination of characterization techniques is utilized, that facilitates the non-invasive assessment of CNT dispersion in epoxy produced by the scalable process of calendering. First, the structural parameters of these nanocomposites are evaluated across multiple length scales (10 −10 m to 10− 3 m) using scanning gallium-ion microscopy, transmission electron microscopy and small-angle neutron scattering. Then, a non-contact resonant microwave cavity perturbation (RCP) technique is employed to accurately measure the AC electrical conductivity of the nanocomposites. Quantitative correlations between the conductivity and structural parameters find the RCP measurements to be sensitive to CNT mass fraction, spatial organization and, therefore, the processing parameters. These results, and the non-contact nature and speed of RCP measurements identify this technique as being ideally suited for quality control of CNT nanocomposites in a nanomanufacturing environment. When validated by the multiscale characterization suite, RCP may be broadly applicable in the production of hybrid functional materials, such as graphene, gold nanorod, and carbon black nanocomposites. Graphical abstract: